Psikolinguistik Dalam Perspektif Digital: Pengaruh Media Sosial Terhadap Produksi Bahasa Mahasiswa - Aulia Nur Khotimah; Muhammad Hasyimsyah Batubara (Journal of Educational Research and Learning Analytics, 2025)
This study analyzes the influence of social media on students' language production from a psycholinguistic perspective, highlighting how digital interactions shape linguistic behavior and cognitive processes in language production. Digital technology has changed students' communication patterns and given rise to new forms of language such as abbreviations, emoticons, code-mixing, and syntactic simplification. Using a descriptive qualitative approach through documentation and conversation observation, this study identifies linguistic phenomena on WhatsApp, Instagram, and TikTok. The analysis is based on Levelt's speech production model, which includes the stages of conceptualization, formulation, and articulation. The results show that social media influences speech planning, lexical selection, and syntactic arrangement. Preliminary quantitative indications regarding the frequency of digital language use enrich the perspective of learning analytics. The study concludes that social media is a space for the formation of students' linguistic identity and has implications for digital literacy and academic language competence.